Blood pressure and renal outcomes after renal artery aneurysm intervention: Single-center experience and review of literature - Li, Siting; Li, Fangda; Liu, Zhili; Zeng, Rong; Ye, Wei; Shao, Jiang; Zheng, Yuehong (Frontiers in Cardiovascular Medicine, 2023)
Objective To explore the results of hypertension improvement and renal function preservation after renal artery aneurysm (RAA) repair. Methods This study retrospectively analyzed the change in blood pressure (BP) and renal outcomes of 59 RAA patients throughout either open or endovascular operations and follow-up at a large center. Patients were grouped according to the difference in their BP at the last follow-up vs. their baseline value. Logistic regression was conducted to explore risk factors for perioperative BP relief and long-term hypertension reonset. Previous studies of RAA with records of BP, blood creatinine level, or GFR/eGFR results are reviewed. Results Hypertension was observed in 62.7% (37/59) of the patients included. Postoperative BP declined from 132.20 ± 16.46/79.92 ± 9.64 mmHg to 122.41 ± 11.17/71.10 ± 9.82 mmHg, while eGFR changed from 108.17 ± 24.73 to 98.92 ± 23.87 ml/min/1.73 m2. The median follow-up was 854 [IQR: 1,405] days. Both open and endovascular techniques significantly relieved hypertension and did not impair renal function much. Lower preoperative systolic BP (SBP) was significantly associated with hypertension relief (OR = 0.83, 95% CI: 0.70–0.99). Among patients with normal BP after the operation, higher postoperative SBP was significantly associated with new-onset hypertension (OR = 1.14, 95% CI: 1.01–1.29). Literature review indicated that renal function usually remained normal at follow-up, whereas relief of hypertension varied. Conclusion Patients with lower preoperative SBP were likely to benefit more from the operation, while higher postoperative SBP indicated a higher chance of hypertension reonset. Creatinine level and eGFR generally remained stable regardless of operation type.